Amyloplast displacement is necessary for gravisensing in Arabidopsis shoots as revealed by a centrifuge microscope. (14th October 2013) - Toyota, Masatsugu; Ikeda, Norifumi; Sawai‐Toyota, Satoe; Kato, Takehide; Gilroy, Simon; Tasaka, Masao; Morita, Miyo Terao
Summary: The starch‐statolith hypothesis proposes that starch‐filled amyloplasts act as statoliths in plant gravisensing, moving in response to the gravity vector and signaling its direction. However, recent studies suggest that amyloplasts show continuous, complex movements in Arabidopsis shoots, contradicting the idea of a so‐called 'static' or 'settled' statolith. Here, we show that amyloplast movement underlies shoot gravisensing by using a custom‐designed centrifuge microscope in combination with analysis of gravitropic mutants. The centrifuge microscope revealed that sedimentary movements of amyloplasts under hypergravity conditions are linearly correlated with gravitropic curvature in wild‐type stems. We next analyzed the hypergravity response in the shoot gravitropism 2 ( sgr2 ) mutant, which exhibits neither a shoot gravitropic response nor amyloplast sedimentation at 1 g . sgr2 mutants were able to sense and respond to gravity under 30 g conditions, during which the amyloplasts sedimented. These findings are consistent with amyloplast redistribution resulting from gravity‐driven movements triggering shoot gravisensing. To further support this idea, we examined two additional gravitropic mutants, phosphoglucomutase ( pgm ) and sgr9, which show abnormal amyloplast distribution and reduced gravitropism at 1 g . We found that the correlation between hypergravity‐induced amyloplast sedimentation and gravitropic curvature of these mutants was identical to that of wild‐type plants. These observations suggest that Arabidopsis shoots have a gravisensing mechanism that linearly converts the number of amyloplasts that settle to the 'bottom' of the cell into gravitropic signals. Further, the restoration of the gravitropic response by hypergravity in the gravitropic mutants that we tested indicates that these lines probably have a functional gravisensing mechanism that is not triggered at 1 g .